The Saccharina latissima microbiome: Effects of region, season, and physiology - Burgunter-Delamare, Bertille; Rousvoal, Sylvie; Legeay, Erwan; Tanguy, Gwenn; Fredriksen, Stein; Boyen, Catherine; Dittami, Simon M. (Frontiers in Microbiology, 2023)
Saccharina latissima is a canopy-forming species of brown algae and, as such, is considered an ecosystem engineer. Several populations of this alga are exploited worldwide, and a decrease in the abundance of S. latissima at its southern distributional range limits has been observed. Despite its economic and ecological interest, only a few data are available on the composition of microbiota associated with S. latissima and its role in algal physiology. We studied the whole bacterial community composition associated with S. latissima samples from three locations (Brittany, Helgoland, and Skagerrak) by 16S metabarcoding analyses at different scales: algal blade part, regions, season (at one site), and algal physiologic state. We have shown that the difference in bacterial composition is driven by factors of decreasing importance: (i) the algal tissues (apex/meristem), (ii) the geographical area, (iii) the seasons (at the Roscoff site), and (iv) the algal host’s condition (healthy vs. symptoms). Overall, Alphaproteobacteria, Gammaproteobacteria, and Bacteroidia dominated the general bacterial communities. Almost all individuals hosted bacteria of the genus Granulosicoccus, accounting for 12% of the total sequences, and eight additional core genera were identified. Our results also highlight a microbial signature characteristic for algae in poor health independent of the disease symptoms. Thus, our study provides a comprehensive overview of the S. latissima microbiome, forming a basis for understanding holobiont functioning.